OPTIMALISASI PEMANFAATAN PANGAN LOKAL DALAM PEMBUATAN MAKANAN SEHAT BALITA STUNTING - Reineldis Elsidianastika Trisnawati; Jayanthi P. Janggu; Putriatri K. Senudin; Christin F. M. Bebok; Maria C. Mon (LPPM Universitas Bina Bangsa, 2023)
Nutrition problems are still a major problem in various developing countries including Indonesia. Lack of nutritional intake in toddlers can have an impact on the health of the child, one of which is that children can experience stunting. The results of the Basic Health Research in 2018 showed that the prevalence rate of stunting in NTT Province reached 42.6%. Compang Dalo Village is one village in Ruteng District, Manggarai Regency that has quite a lot of stunting cases. Partner's lack of knowledge about child nutrition during the first 1000 days of life can be a cause of stunting. Therefore, various efforts are needed that can be done in preventing stunting such as health promotion and empowerment. The purpose of this activity is to increase people's knowledge and skills in utilizing local food to make healthy food for toddlers. The method of activity is through counseling on stunting and training on making healthy food from local food, namely Moringa leaf noodles. The results of the activity have a positive impact on partners. During the activity the partners were very happy and enthusiastic because they gained new knowledge about stunting and gained experience making healthy and nutritious food from Moringa leaves